Formaldehyde-free adhesive as well as preparation method and application thereof
Through the combination of modified lignin solutions and other auxiliary materials, a formal aldehyde -free adhesive is prepared, which solves the problem of lack of harmful substances in existing adhesives, and realizes high -performance, environmentally friendly adhesives. The production of artificial board.
Patent Information
- Application Number
- CN202410576006.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-10
AI Technical Summary
The release of harmful substances such as formaldehyde in existing artificial board adhesives is insufficient in flame retardancy and mechanical properties, making it difficult to meet environmental protection and performance requirements.
Use modified lignin solution, polyurethane lotion, curing agent, modified filler, and modified flame retardant (such as Mongolian soil and talc powder) to prepare aldehyde -free glue adhesives and modifiers and modified modifiers and modified hydroxyethyls. The compatibility of sexual fillers improves the flame retardability and mechanical properties of the adhesive.
The environmental protection, good flame retardant, and strong mechanical properties of aldehyde -free adhesives are suitable for preparation of artificial boards, especially the production of plywood and particleboard.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive preparation, and in particular relates to a formaldehyde-free adhesive that can be used for artificial boards, and a preparation method and application thereof. Background Art
[0002] Artificial boards mainly include plywood, particleboard and fiberboard. In the processing and manufacturing process of the above-mentioned artificial boards, adhesives are inevitably used. Taking particleboard as an example, it is usually processed into chips from wood processing residues, logging residues, small-diameter wood or wood plant fiber raw materials, and then pressed with adhesives.
[0003] The adhesives used in the processing of artificial boards are mainly urea-formaldehyde glue, phenol-formaldehyde glue and melamine-formaldehyde glue. The usage of the above-mentioned "three-formaldehyde glue" accounts for about 90% of the adhesives used in the wood industry. Urea-formaldehyde glue is used the most because of its low price and excellent performance; but its water resistance is poor, especially its resistance to boiling water is very poor; most of this type of plywood will automatically open in two hours in boiling water; therefore, urea-formaldehyde glue is mainly used in indoor environments where its water resistance and weather resistance are not required to be high, such as for the production of particleboard, fiberboard and plywood. Phenolic glue is an adhesive with better performance than urea-formaldehyde glue, and its resistance to boiling water is good, but the price is relatively high; it is mainly used in outdoor environments, such as for the production of concrete plywood formwork, and some are used for the impregnation of the bottom paper in high-pressure decorative laminates. Melamine-formaldehyde glue has excellent water resistance and heat resistance, but its price is relatively expensive.
[0004] With the increasing awareness of environmental protection, the formaldehyde content of adhesives used in the production of artificial boards has received increasing attention. The above-mentioned "trialdehyde glue" releases more or less harmful substances such as formaldehyde during use, so new formaldehyde-free / low-formaldehyde adhesives have received attention. At present, there are two major types of formaldehyde-free adhesives that are being developed, one is isocyanate glue, and the other is modified biomass glue. When isocyanate adhesives are used to prepare particleboards, their advantage is that they can strongly bond the shredded wood with a high moisture content together, and the prepared particleboard will not release harmful substances such as formaldehyde during use. However, the disadvantage of isocyanate adhesives is that they have no initial adhesion, and require the addition of tackifiers and other processes. The operating process is complicated and the cost increases accordingly. Modified biomass adhesives are mostly used in industrial production, including starch-based adhesives and soy protein-based adhesives. This type of biomass adhesive has gradually entered the field of research. In the prior art, for example, patent document CN107033832A provides a method for preparing a composite adhesive using cottonseed meal, and patent document CN109517576A provides a method for preparing an adhesive using defatted soybean meal protein powder.
[0005] Lignin is a biomass resource second only to cellulose. Industrial lignin often comes from industries such as papermaking and biorefining. Strengthening the reuse of lignin resources has both economic and environmental benefits. Therefore, it is very important to process lignin into an adhesive for the preparation of artificial boards. For example, patent document CN117821012A provides a method for preparing an adhesive using black liquor lignin; a master's thesis (Xu Wenbiao. Research on the preparation of formaldehyde-free adhesives by laccase activation of cellulose ethanol lignin [D]. Beihua University, 2015.) provides a report on the preparation of adhesives by laccase activation of lignin. However, the above documents only focus on the resource utilization of lignin, and do not pay attention to other properties that the prepared adhesives may require during the use of artificial boards, such as flame retardancy and mechanical properties.
[0006] Therefore, the present invention hopes to provide an adhesive which is formaldehyde-free and has excellent performance and takes lignin as raw material. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a formaldehyde-free adhesive and a preparation method and application thereof, which is formaldehyde-free and highly environmentally friendly; has certain flame retardancy, and has excellent mechanical properties and good comprehensive performance.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] First, a formaldehyde-free adhesive is provided, which is prepared from the following raw materials, in parts by weight: 80 to 150 parts of a modified lignin solution, 10 to 30 parts of a polyurethane emulsion, 15 to 35 parts of a curing agent, 6 to 12 parts of a modified filler, and 5 to 15 parts of a flame retardant;
[0010] Wherein, the preparation of the flame retardant comprises the following steps:
[0011] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, and after the addition is completed, maintaining slow stirring conditions for heating treatment, after the treatment is completed, completely evaporating the ethanol solvent, and then washing and drying to obtain pre-modified montmorillonite;
[0012] S12, preparing an aqueous solution of polydiallyldimethylammonium chloride for standby use; then adding the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride, stirring under heating conditions; after the treatment is completed, centrifuging, filtering, and drying to obtain modified montmorillonite;
[0013] S13, adding talcum powder into water to obtain a talcum powder suspension for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension, stirring, centrifuging, washing and drying to obtain the flame retardant.
[0014] In some preferred technical solutions, in step S11, the mass ratio of montmorillonite, ethanol, and concentrated sulfuric acid is 1:4-8:0.04-0.08;
[0015] The temperature of the heating treatment is 25-35°C, and the treatment time is 0.5-4h.
[0016] In some preferred technical solutions, in step S12, the concentration of the aqueous solution of polydiallyldimethylammonium chloride is 1.2-2 g / L;
[0017] The mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.8-1.5:1;
[0018] The heating temperature is 25-35°C and the stirring treatment time is 0.5-4h.
[0019] In some preferred technical solutions, in step S13, the concentration of the talc suspension is 0.8-1.5 g / L;
[0020] The mass ratio of talc powder to modified montmorillonite is 0.6-0.8:1;
[0021] The stirring treatment temperature is 25-35°C and the treatment time is 0.5-2h.
[0022] In some preferred technical solutions, the preparation of the modified lignin solution comprises the following steps:
[0023] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 11.5-12.5, and then treat under heating; after the treatment is completed, a modified lignin solution is obtained;
[0024] Wherein, the concentration of the sodium hydroxide solution is 25-35wt%, and the concentration of the glyoxal solution is 35-45wt%;
[0025] The dosage ratio of glyoxal to straw lignin is 1:2-4;
[0026] The heating treatment temperature is 55-70°C and the treatment time is 2-8h.
[0027] In some preferred technical solutions, the preparation of the modified filler includes the following steps:
[0028] S21, first prepare an alumina suspension; then add KH550 to the obtained suspension, and then heat it under stirring; after the treatment, filter it, dry it, and then perform high-energy ball milling to obtain material I;
[0029] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, and heating under stirring; after the treatment is completed, centrifuging, washing, and drying to obtain material II;
[0030] S23, adding the material I obtained in step S21 and the material II obtained in step S22 into deionized water respectively, stirring them, and after the treatment, filtering, washing and drying them to obtain the modified filler.
[0031] In some preferred technical solutions, in step S21, the concentration of the alumina suspension is 12-18 wt %, the mass ratio of alumina to KH550 is 100:5-15, the heating treatment temperature is 65-75° C., and the treatment time is 0.5-4 h;
[0032] In step S22, the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:20-30:5-10:2.5-4, the heating treatment temperature is 25-35°C, and the treatment time is 2-6h;
[0033] In step S23, the mass ratio of material I to material II is 1:0.5-2; the stirring treatment temperature is 25-35°C, and the treatment time is 0.5-4h.
[0034] In some preferred technical solutions, the curing agent is selected from one or two of epichlorohydrin and triethylenediamine.
[0035] Secondly, the present invention also provides a method for preparing the above-mentioned formaldehyde-free adhesive, comprising the following steps:
[0036] While maintaining stirring, add the polyurethane emulsion to the modified lignin solution; after stirring evenly, add the curing agent, modified filler and flame retardant, and stir evenly again to obtain the formaldehyde-free adhesive.
[0037] Finally, the present invention hopes to protect the application of the above-mentioned formaldehyde-free adhesive in many processing fields including the preparation of artificial boards.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The formaldehyde-free adhesive provided by the invention uses a modified lignin solution as a main raw material and is supplemented by the use of a portion of polyurethane emulsion, thereby ensuring that the adhesive is formaldehyde-free.
[0040] The formaldehyde-free adhesive provided by the present invention uses the industrial lignin byproduct as a raw material in the modified lignin solution, and is specifically modified by hydroxyethylation, the purpose of which is to introduce hydroxyl groups and improve its compatibility with flame retardants and fillers; at the same time, the reaction activity of the lignin modified by hydroxyethylation is improved, which is conducive to the compounding use of the polyurethane emulsion system. It should be particularly emphasized that compared with the commonly used formaldehyde modification, the modified substance glyoxal used in the present invention has low toxicity.
[0041] The formaldehyde-free adhesive provided by the present invention has certain flame retardant properties by introducing the use of flame retardants. Common halogen-containing flame retardants have certain toxicity. The present invention selects common montmorillonite and talcum powder as the core materials of the flame retardant. Montmorillonite and talcum powder both have certain flame retardant effects, but there are problems such as dispersibility during use, and the direct use of the performance of the two separately cannot fully exert the effects of the two. Therefore, the present invention chooses to modify them to a certain extent. Specifically, the present invention first uses concentrated sulfuric acid to pre-modify the montmorillonite, remove impurities and preliminarily dredge the pores; then, polydiallyldimethylammonium chloride is used to perform secondary treatment on the montmorillonite, which is beneficial to the intercalation treatment of the montmorillonite on the one hand, and further improves its subsequent composite ability; on the other hand, it is beneficial to introduce positive charges and amino groups on the surface or pores of the montmorillonite. The montmorillonite treated as above is conducive to the talc (containing rich hydroxyl groups and having negative surface charge) to form a compound system with the modified montmorillonite in various forms such as hydrogen bonding and positive and negative charge combination, thereby improving the dispersibility of the talc, reducing its agglomeration performance, and being conducive to exerting its flame retardant effect.
[0042] The formaldehyde-free adhesive provided by the present invention has the purpose of improving the comprehensive properties of the adhesive, such as mechanical properties, by introducing modified fillers. Silica and alumina are two common fillers, which are toughening and wear-resistant. Alumina is harder, and silica is relatively soft. The combination of the two can play the greatest effect. The present invention also makes corresponding modifications for the use of the two. Specifically: the alumina is modified with KH550 and then subjected to high-energy ball milling. On the one hand, the dispersibility of alumina is guaranteed. On the other hand, the activity of the alumina surface is improved by high-energy ball milling, which is convenient for subsequent compounding with silica and improving the compatibility in modified lignin and polyurethane emulsion; the carboxylation treatment of silica, on the one hand, is conducive to the composite combination with the modified alumina, and on the other hand, it is conducive to improving the compatibility with the modified lignin solution rich in hydroxyl groups. The two can form a carboxyl-hydroxyl hydrogen bond to ensure the uniformity of dispersion. Obviously, after a simple blending, the treated silica and alumina can be fully dispersed and densely filled in the adhesive system, thus ensuring the performance of the adhesive.
[0043] In summary, the adhesive provided by the present invention is formaldehyde-free and has good comprehensive performance, and is suitable for the preparation of artificial boards, and can be specifically used for the production of artificial boards such as plywood and particleboard. DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0045] In the embodiment of the present invention, the straw lignin is corn straw lignin, which is purchased from outside, and its main physical and chemical properties are: lignin content is about 90%, moisture is 3.4%, ash is 4.5%, and pH value is 4.6.
[0046] In the present invention, the particle size of aluminum oxide is about 100 mesh.
[0047] The high-energy ball mill used in the present invention can be a common device on the market, such as a ball mill of model TV400-6.
[0048] The concentration of concentrated sulfuric acid used in the present invention is 96%.
[0049] The polyurethane emulsion used in the present invention can be a common emulsion type. For example, the polyurethane emulsion used in the present invention is PU-106, which is purchased from Hefei Dibang Nanotechnology Co., Ltd.
[0050] In the present invention, the molecular weight of the polydiallyldimethylammonium chloride is 10,000 to 20,000 and is produced by Sigma-Aldrich Company of the United States.
[0051] The remaining silicon dioxide, ethanol, talcum powder, etc. used were purchased from the market.
[0052] Example 1
[0053] A formaldehyde-free adhesive is prepared from the following raw materials, by weight: 100 g of modified lignin solution, 20 g of polyurethane emulsion, 15 g of curing agent, 10 g of modified filler, and 10 g of flame retardant;
[0054] Wherein, the preparation of the flame retardant comprises the following steps:
[0055] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0056] S12, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.5 g / L for later use; then add the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.85:1), and stir at 30°C for 1.5 hours; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0057] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.7:1), stirring at 25°C for 1 hour, centrifuging, washing and drying to obtain the flame retardant.
[0058] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0059] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0060] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0061] The dosage ratio of glyoxal to straw lignin was 1:3;
[0062] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0063] Wherein, the preparation of the modified filler comprises the following steps:
[0064] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0065] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0066] S23. Add material I obtained in step S21 and material II obtained in step S22 into deionized water at a mass ratio of 1:1, respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0067] In this embodiment, a method for preparing the above-mentioned formaldehyde-free glue is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution under stirring conditions; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0068] Example 2
[0069] A formaldehyde-free adhesive is prepared from the following raw materials, by weight: 100 g of modified lignin solution, 22 g of polyurethane emulsion, 16 g of curing agent, 9 g of modified filler, and 11 g of flame retardant;
[0070] Wherein, the preparation of the flame retardant comprises the following steps:
[0071] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2.5 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0072] S12, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.4 g / L for later use; then add the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.85:1), and stir at 30°C for 2 hours; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0073] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 0.9 g / L for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.75:1), stirring at 25°C for 1.5 hours, centrifuging, washing and drying to obtain the flame retardant.
[0074] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0075] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 11.8, and then treat under heating; after the treatment is completed, a modified lignin solution is obtained;
[0076] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0077] The dosage ratio of glyoxal to straw lignin was 1:3;
[0078] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0079] Wherein, the preparation of the modified filler comprises the following steps:
[0080] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0081] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0082] S23. Add material I obtained in step S21 and material II obtained in step S22 into deionized water at a mass ratio of 1:1, respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0083] In this embodiment, a method for preparing the above-mentioned formaldehyde-free glue is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution under stirring conditions; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0084] Example 3
[0085] A formaldehyde-free adhesive is prepared from the following raw materials, by weight: 100 g of modified lignin solution, 18 g of polyurethane emulsion, 15 g of curing agent, 11 g of modified filler, and 9 g of flame retardant;
[0086] Wherein, the preparation of the flame retardant comprises the following steps:
[0087] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0088] S12, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.4 g / L for later use; then add the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.85:1), and stir at 30°C for 1.5 hours; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0089] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.75:1), stirring at 25°C for 1.5 hours, centrifuging, washing and drying to obtain the flame retardant.
[0090] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0091] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0092] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0093] The dosage ratio of glyoxal to straw lignin was 1:3;
[0094] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0095] Wherein, the preparation of the modified filler comprises the following steps:
[0096] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0097] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0098] S23. Add material I obtained in step S21 and material II obtained in step S22 into deionized water at a mass ratio of 1:1, respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0099] In this embodiment, a method for preparing the above-mentioned formaldehyde-free glue is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution under stirring conditions; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0100] Comparative Example 1
[0101] Compared with Example 1, this comparative example eliminates step S11. Specifically, this comparative example provides a formaldehyde-free adhesive, which is prepared from the following raw materials by weight: 100 g of modified lignin solution, 20 g of polyurethane emulsion, 15 g of curing agent, 10 g of modified filler, and 10 g of flame retardant;
[0102] Wherein, the preparation of the flame retardant comprises the following steps:
[0103] S11, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.5 g / L for later use; then add montmorillonite to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to montmorillonite is 0.85:1), and stir at 30° C. for 1.5 h; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0104] S12, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the modified montmorillonite obtained in step S11 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.7:1), stirring at 25°C for 1 hour, centrifuging, washing and drying to obtain the flame retardant.
[0105] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0106] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0107] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0108] The dosage ratio of glyoxal to straw lignin was 1:3;
[0109] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0110] Wherein, the preparation of the modified filler comprises the following steps:
[0111] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0112] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0113] S23. Add material I obtained in step S21 and material II obtained in step S22 into deionized water at a mass ratio of 1:1, respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0114] In this comparative example, a method for preparing the above-mentioned formaldehyde-free adhesive is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution while maintaining stirring; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0115] Comparative Example 2
[0116] Compared with Example 1, this comparative example eliminates step S12. Specifically, this comparative example provides a formaldehyde-free adhesive, which is prepared from the following raw materials by weight: 100 g of modified lignin solution, 20 g of polyurethane emulsion, 15 g of curing agent, 10 g of modified filler, and 10 g of flame retardant;
[0117] Wherein, the preparation of the flame retardant comprises the following steps:
[0118] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0119] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the pre-modified montmorillonite obtained in step S11 into the talcum powder suspension (the mass ratio of talcum powder to pre-modified montmorillonite is 0.7:1), stirring at 25°C for 1 hour, centrifuging, washing and drying to obtain the flame retardant.
[0120] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0121] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0122] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0123] The dosage ratio of glyoxal to straw lignin was 1:3;
[0124] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0125] Wherein, the preparation of the modified filler comprises the following steps:
[0126] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0127] S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0128] S23. Add material I obtained in step S21 and material II obtained in step S22 into deionized water at a mass ratio of 1:1, respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0129] In this comparative example, a method for preparing the above-mentioned formaldehyde-free adhesive is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution while maintaining stirring; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0130] Comparative Example 3
[0131] Compared with Example 1, this comparative example eliminates step S21. Specifically, this comparative example provides a formaldehyde-free adhesive, which is prepared from the following raw materials by weight: 100 g of modified lignin solution, 20 g of polyurethane emulsion, 15 g of curing agent, 10 g of modified filler, and 10 g of flame retardant;
[0132] Wherein, the preparation of the flame retardant comprises the following steps:
[0133] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0134] S12, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.5 g / L for later use; then add the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.85:1), and stir at 30°C for 1.5 hours; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0135] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.7:1), stirring at 25°C for 1 hour, centrifuging, washing and drying to obtain the flame retardant.
[0136] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0137] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0138] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0139] The dosage ratio of glyoxal to straw lignin was 1:3;
[0140] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0141] Wherein, the preparation of the modified filler comprises the following steps:
[0142] S21, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, stirring at 25°C for 4 hours; after the treatment, centrifuging, washing and drying to obtain material II; wherein the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:25:6:3;
[0143] S22. Add alumina (same amount as in Example 1) and material II obtained in step S21 into deionized water respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0144] In this comparative example, a method for preparing the above-mentioned formaldehyde-free adhesive is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution while maintaining stirring; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0145] Comparative Example 4
[0146] Compared with Example 1, this comparative example eliminates step S22. Specifically, this comparative example provides a formaldehyde-free adhesive, which is prepared from the following raw materials by weight: 100 g of modified lignin solution, 20 g of polyurethane emulsion, 15 g of curing agent, 10 g of modified filler, and 10 g of flame retardant;
[0147] Wherein, the preparation of the flame retardant comprises the following steps:
[0148] S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, maintaining slow stirring conditions at 30°C for 2 hours, and after the treatment, completely evaporating the ethanol solvent (heating treatment), followed by washing and drying to obtain pre-modified montmorillonite; wherein the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:5:0.05;
[0149] S12, prepare an aqueous solution of polydiallyldimethylammonium chloride with a concentration of 1.5 g / L for later use; then add the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride (the mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.85:1), and stir at 30°C for 1.5 hours; after the treatment is completed, centrifuge, filter, and dry to obtain modified montmorillonite;
[0150] S13, adding talcum powder into water to prepare a talcum powder suspension with a concentration of 1 g / L for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension (the mass ratio of talcum powder to modified montmorillonite is 0.7:1), stirring at 25°C for 1 hour, centrifuging, washing and drying to obtain the flame retardant.
[0151] Wherein, the preparation of the modified lignin solution comprises the following steps:
[0152] Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring conditions, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 12, and then treat under heating conditions; after the treatment is completed, a modified lignin solution is obtained;
[0153] Wherein, the concentration of sodium hydroxide solution is 30wt%, and the concentration of glyoxal solution is 36wt%;
[0154] The dosage ratio of glyoxal to straw lignin was 1:3;
[0155] The heating treatment temperature is 60°C and the treatment time is 4 hours.
[0156] Wherein, the preparation of the modified filler comprises the following steps:
[0157] S21, first prepare a 15wt% alumina suspension; then add KH550 (the mass ratio of alumina to KH550 is 100:9) to the obtained suspension, and then treat it at 70°C for 2h under stirring conditions; after the treatment is completed, filter and dry it, and then perform high-energy ball milling (35min) to obtain material I;
[0158] S22. Add material I and silicon dioxide obtained in step S22 into deionized water respectively, and stir (25°C, 2h). After the treatment, filter, wash and dry to obtain the modified filler.
[0159] In this comparative example, a method for preparing the above-mentioned formaldehyde-free adhesive is also provided, comprising the following steps: adding polyurethane emulsion to the modified lignin solution while maintaining stirring; adding epichlorohydrin, modified filler and flame retardant after stirring evenly, and stirring evenly again to obtain the formaldehyde-free adhesive.
[0160] The adhesives prepared in Example 1 and Comparative Examples 1 to 4 were heated at 400 g / m 2 The double-sided glue coating amount was applied on a poplar veneer (270mm×270mm×1.6mm), and hot pressed (hot pressing temperature 135℃, hot pressing pressure 1.3MPa, time 6min) to obtain a three-layer plywood. Then, the performance test of the above three-layer plywood was carried out, as follows:
[0161] The bonding strength test is carried out in accordance with GB / T17657-2022. After cold water immersion (25°C, 24h) or hot water immersion (63°C, 3h), the bonding strength test is carried out after sufficient drying at 73°C.
[0162] The flame retardant performance of the above three-layer plywood was tested with reference to GB / T14656-2009.
[0163] The water resistance of the above three-layer plywood was tested with reference to GB / T17657-2022, and the 24h water absorption results were recorded.
[0164] The formaldehyde emission of the above three-layer plywood was tested with reference to GB / T17657-2022.
[0165] The test results are shown in Table 1.
[0166] Table 1
[0167]
[0168]
[0169] It can be seen from Table 1 that the plywood prepared by the formaldehyde-free adhesive provided by the present invention has good mechanical properties, good flame retardancy, good water resistance and good comprehensive performance.
[0170] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A formaldehyde-free adhesive, characterized in that: The invention is prepared from the following raw materials in parts by weight: 80 to 150 parts of modified lignin solution, 10 to 30 parts of polyurethane emulsion, 15 to 35 parts of curing agent, 6 to 12 parts of modified filler, and 5 to 15 parts of flame retardant; Wherein, the preparation of the flame retardant comprises the following steps: S11, adding montmorillonite to an ethanol solvent, stirring and then slowly adding concentrated sulfuric acid, and after the addition is completed, maintaining slow stirring conditions for heating treatment, after the treatment is completed, completely evaporating the ethanol solvent, and then washing and drying to obtain pre-modified montmorillonite; S12, preparing an aqueous solution of polydiallyldimethylammonium chloride for standby use; then adding the pre-modified montmorillonite obtained in step S11 to the aqueous solution of polydiallyldimethylammonium chloride, stirring under heating conditions; after the treatment is completed, centrifuging, filtering, and drying to obtain modified montmorillonite; S13, adding talcum powder into water to obtain a talcum powder suspension for later use; then, adding the modified montmorillonite obtained in step S12 into the talcum powder suspension, stirring, centrifuging, washing and drying to obtain the flame retardant.
2. The formaldehyde-free adhesive according to claim 1, characterized in that: In step S11, the mass ratio of montmorillonite, ethanol and concentrated sulfuric acid is 1:4-8:0.04-0.08; The temperature of the heating treatment is 25-35°C, and the treatment time is 0.5-4h.
3. The formaldehyde-free adhesive according to claim 1, characterized in that: In step S12, the concentration of the aqueous solution of polydiallyldimethylammonium chloride is 1.2 to 2 g / L; The mass ratio of polydiallyldimethylammonium chloride to pre-modified montmorillonite is 0.8-1.5:1; The heating temperature is 25-35°C and the stirring treatment time is 0.5-4h.
4. The formaldehyde-free adhesive according to claim 1, characterized in that: In step S13, the concentration of the talcum powder suspension is 0.8-1.5 g / L; The mass ratio of talc powder to modified montmorillonite is 0.6-0.8:1; The stirring treatment temperature is 25-35°C and the treatment time is 0.5-2h.
5. The formaldehyde-free adhesive according to claim 1, characterized in that: The preparation of the modified lignin solution comprises the following steps: Prepare a sodium hydroxide solution and a glyoxal solution for later use; then, add the straw lignin to the sodium hydroxide solution under rapid stirring, stir evenly, then slowly add the glyoxal solution and adjust the pH value of the system to 11.5-12.5, and then treat under heating; after the treatment is completed, a modified lignin solution is obtained; Wherein, the concentration of the sodium hydroxide solution is 25-35wt%, and the concentration of the glyoxal solution is 35-45wt%; The dosage ratio of glyoxal to straw lignin is 1:2-4; The heating treatment temperature is 55-70°C and the treatment time is 2-8h.
6. The formaldehyde-free adhesive according to claim 1, characterized in that: The preparation of the modified filler comprises the following steps: S21, first prepare an alumina suspension; then add KH550 to the obtained suspension, and then heat it under stirring; after the treatment, filter it, dry it, and then perform high-energy ball milling to obtain material I; S22, adding silica to DMF solvent, stirring evenly, then adding KH550 and succinic anhydride, and heating under stirring; after the treatment is completed, centrifuging, washing, and drying to obtain material II; S23, adding the material I obtained in step S21 and the material II obtained in step S22 into deionized water respectively, stirring them, and after the treatment, filtering, washing and drying them to obtain the modified filler.
7. The formaldehyde-free adhesive according to claim 6, characterized in that: In step S21, the concentration of the alumina suspension is 12-18 wt %, the mass ratio of alumina to KH550 is 100:5-15, the heating treatment temperature is 65-75° C., and the treatment time is 0.5-4 h; In step S22, the mass ratio of silica, DMF, KH550 and succinic anhydride is 1:20-30:5-10:2.5-4, the heating treatment temperature is 25-35°C, and the treatment time is 2-6h; In step S23, the mass ratio of material I to material II is 1:0.5-2; the stirring treatment temperature is 25-35°C, and the treatment time is 0.5-4h.
8. The formaldehyde-free adhesive according to claim 1, characterized in that: The curing agent is selected from one or two of epichlorohydrin and triethylenediamine.
9. A method for preparing the formaldehyde-free adhesive according to any one of claims 1 to 8, characterized in that: The steps include: While maintaining stirring, add the polyurethane emulsion to the modified lignin solution; after stirring evenly, add the curing agent, modified filler and flame retardant, and stir evenly again to obtain the formaldehyde-free adhesive.
10. Use of the formaldehyde-free adhesive according to any one of claims 1 to 8 in the preparation of artificial boards.
Citation Information
Patent Citations
Formaldehyde-free adhesive for artificial boards and preparation method of formaldehyde-free adhesive
CN107033832A
Formaldehyde-free protein adhesive and preparation method thereof
CN109517576A
Lignin-based formaldehyde-free adhesive and preparation method thereof
CN117821012A
Method of producing aldehyde-free lignin-based wood adhesive by using lignin
CN107286905A
Flame-retardant nano composite material and preparation method thereof
CN107936370A
Cited By
Formaldehyde-free adhesive based on activated lignin and preparation method thereof
CN121271503A